2021
DOI: 10.1021/acs.chemmater.1c02149
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Prediction and Thin-Film Growth of the Defect-Tolerant Nitride Semiconductor YZn3N3

Abstract: Ternary zinc nitrides are of particular interest for solar energy conversion because they can be entirely manufactured from earth-abundant components and possess suitable band structures. Although exhaustive computational explorations and experimental verifications of ternary zinc nitrides have been reported, there have hitherto been no studies of YZn 3 N 3 . We conducted first-principles calculations to predict its crystal and electronic structures, optical properties, and defect chemistry. Our calculations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…50 Oba and co-workers theoretically predicted a defect-tolerant ternary nitride YZn 3 N 3 with a hexagonal ScAl 3 C 3 type crystal structure. 51 Thin films grown by reactive cosputtering have a band gap of 1.84 eV, in agreement with theoretical predictions. First-principles defect calculations showed that all native point defects are shallow, except the nitrogen vacancy (V N introduces a shallow state 0.24 eV below the conduction band minimum).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…50 Oba and co-workers theoretically predicted a defect-tolerant ternary nitride YZn 3 N 3 with a hexagonal ScAl 3 C 3 type crystal structure. 51 Thin films grown by reactive cosputtering have a band gap of 1.84 eV, in agreement with theoretical predictions. First-principles defect calculations showed that all native point defects are shallow, except the nitrogen vacancy (V N introduces a shallow state 0.24 eV below the conduction band minimum).…”
supporting
confidence: 82%
“…However, these nitrides are defect intolerant because of significant cation disorder and presence of deep defects . Oba and co-workers theoretically predicted a defect-tolerant ternary nitride YZn 3 N 3 with a hexagonal ScAl 3 C 3 type crystal structure . Thin films grown by reactive cosputtering have a band gap of 1.84 eV, in agreement with theoretical predictions.…”
Section: Chalcogenide Perovskitessupporting
confidence: 62%
“…Subsequently, the same researchers have demonstrated heteroepitaxial growth of CaZn 2 N 2 by MBE with 10 13 cm −3 bipolar doping and 0.3−4.3 cm 2 /(V s) mobility, 162 synthesized bulk polycrystalline SrZn 2 N 2 163 and Ca(Mg 1−x Zn x ) 2 N 2 solid solutions with 1.9−3.3 eV tunable band gaps and extrinsic p-type doping by Na, 164 and reported on sputtered YZn 3 N 3 thin films. 165 Another group focused on hightemperature high-pressure ammonothermal synthesis 166 of nitridophosphates in autoclaves filled with supercritical NH 3 , 167 including polycrystalline Zn 2 PN 3 with 3.7 eV band gap and single crystal Mg 2 PN 3 with 5 eV band gap, both with wurtzite-derived crystal structure where P shares the cation site with Zn or Mg. 168 It would be interesting to synthesize these materials in the epitaxial thin film form on lattice-matched substates because the Mg 2 PN 3 lattice constants are close to GaN (∼1.5% mismatch) and the Zn 2 PN 3 lattice constants are close to AlN (∼0.6% mismatch) Two previously unreported ternary compounds in the Zn− Mo−N materials system, Zn 3 MoN 4 and ZnMoN 2 , 55 were predicted and synthesized in the Zn−Mo−N materials system predicted in ref 25. Both Zn 3 MoN 4 and ZnMoN 2 compositions crystallize in wurtzite-derived structures (Figure 8a), with their solid solutions having a tunable +VI/+IV valence state (Figure 9a), a term coined "redox-mediated stabilization".…”
Section: Experimental Synthesismentioning
confidence: 99%
“…This material exhibited a mixed octahedrally/tetrahedrally coordinated layered crystal structure, a direct 1.9–2.0 eV band gap, and measured near-band gap photoluminescence. Subsequently, the same researchers have demonstrated heteroepitaxial growth of CaZn 2 N 2 by MBE with 10 13 cm –3 bipolar doping and 0.3–4.3 cm 2 /(V s) mobility, synthesized bulk polycrystalline SrZn 2 N 2 and Ca­(Mg 1– x Zn x ) 2 N 2 solid solutions with 1.9–3.3 eV tunable band gaps and extrinsic p-type doping by Na, and reported on sputtered YZn 3 N 3 thin films . Another group focused on high-temperature high-pressure ammonothermal synthesis of nitridophosphates in autoclaves filled with supercritical NH 3 , including polycrystalline Zn 2 PN 3 with 3.7 eV band gap and single crystal Mg 2 PN 3 with 5 eV band gap, both with wurtzite-derived crystal structure where P shares the cation site with Zn or Mg .…”
Section: Experimental Synthesismentioning
confidence: 99%
“…Recent breakthroughs in high-throughput computational techniques successfully predicted many new ternary nitrides, 3 and combinatorial co-sputtering has proven to be a powerful tool for experimentally realizing these predicted materials. [3][4][5][6][7][8][9][10][11][12][13][14][15] In particular, Mg and Zn can be combined with early transition metals and main-group elements to form ternary nitrides that are structurally related to the binary M 3+ N nitrides (e.g., wurtzite GaN or rocksalt TiN). 4 With A as Zn or Mg and M as a main group or transition metal, the stoichiometries A 2+ M 4+ N 2 , A 2 2+ M 5+ N 3 , and A 3 2+ M 6+ N 4 have the 1 : 1 cation : anion ratio of M 3+ N compounds, and semiconducting properties emerge when M is a d 0 transition metal or a main-group element.…”
Section: Introductionmentioning
confidence: 99%